Role of common human TRIM5α variants in HIV-1 disease progression - Ortiz Millàn; Martinez Raquel; May Margaret; Bleiber Gabriela; Goldschmidt Valérie; Telenti Amalio (Retrovirology, 2006)
Abstract Background The retroviral restriction factor tripartite motif protein (TRIM)5α, is characterized by marked amino acid diversity among primates, including specific clusters of residues under positive selection. The identification of multiple non-synonymous changes in humans suggests that TRIM5α variants might be relevant to retroviral pathogenesis. Previous studies have shown that such variants are unlikely to modify susceptibility to HIV-1 infection, or the course of early infection. However, the longterm effect of carrying Trim5α variants on disease progression in individuals infected with HIV-1 has not previously been investigated. Methods In a cohort of 979 untreated individuals infected with HIV-1 with median follow up 3.2 years and 9,828 CD4 T cell measurements, we analysed common amino acid variations: H43Y, V112F, R136Q, G249D, and H419Y. The rate of CD4 T cell decline before treatment was used as the phenotype. In addition, we extended previous work on the in vitro susceptibility of purified donor CD4 T cells (n = 125) to HIV-1 infection, and on the susceptibility of HeLa cells that were stably transduced with the different TRIM5 variants. Haplotypes were analysed according to the most parsimonious evolutionary structure, where two main human TRIM5α groups can be defined according to the residue at amino acid 136. Humans present both Q136 and R136 at similar frequency, and additional TRIM5α amino acid variants are almost exclusively derived from R136-carrying haplotypes. Results We observed modest differences in disease progression for evolutionary branches carrying R136-derived haplotypes, and with the non-synonymous polymorphisms G249D and H419Y. In vitro analysis of susceptibility of donor CD4 T cells, and of the various transduced HeLa cell lines supported the absence of significant differential restriction of HIV-1 infection by the various huTRIM5α alleles. Conclusion Common human variants of TRIM5α have no effect or modest effect on HIV-1 disease progression. These variants occur at sites conserved throughout evolution, and are remote from clusters of positive selection in the primate lineage. The evolutionary value of the substitutions remains unclear.